2015
DOI: 10.1590/s0080-623420150000700014
|View full text |Cite
|
Sign up to set email alerts
|

Carga de trabalho de enfermagem em transplante de células-tronco hematopoiéticas: estudo de coorte

Abstract: RESUMO Objetivo Mensurar a carga de trabalho de enfermagem requerida por pacientes submetidos ao transplante de células-tronco hematopoiéticas (TCTH), autólogo e alogênico e analisar as atividades do Nursing Activities Score (NAS) executadas pela equipe de enfermagem durante a internação para o TCTH. Método Coorte prospectiva realizada de janeiro/2013 a abril/2014 com 62 pacientes internados na unidade de TCTH de um hospital universitário de Campinas/SP, Brasil. Mediu-se a carga de trabalho por meio do NAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
9
0
7
Order By: Relevance
“…The mortality rate associated with treatment is expressed in national and international literature. In Brazil, a study conducted in Campinas-SP, Brazil, with 62 patients submitted to HSCT, showed a death rate of 21% in the period before one year after transplantation 22 . In Iran, a longitudinal study of 587 patients submitted to HSCT revealed that the mean survival time of patients was 517 days 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate associated with treatment is expressed in national and international literature. In Brazil, a study conducted in Campinas-SP, Brazil, with 62 patients submitted to HSCT, showed a death rate of 21% in the period before one year after transplantation 22 . In Iran, a longitudinal study of 587 patients submitted to HSCT revealed that the mean survival time of patients was 517 days 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Nurses were nominally cited as responsible for the care listed in 26 of the primary studies (2,13,(15)(16)(17)(19)(20)(21)(23)(24)27,29,(32)(33)(34)(35)(36)(37)(38)(39)41,(44)(45)(48)(49)(50) , and in the remaining 16 (5,(11)(12)14,18,22,(25)(26)28,(30)(31)40,(42)(43)(46)(47) , the nursing team was mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Care guidance, for execution by patients and family members at home, was investigated in five studies (15)(16)23,(47)(48) . The combination of technical care and guidance provided was thematic studied in 11 studies (5,12,19,(24)(25)(26)40,(42)(43)(44)49) . The indication of the methodological approach and the research design was based on the description of the studies' authors.…”
Section: Resultsmentioning
confidence: 99%
“…O impacto negativo de uma doença afeta diversas áreas da vida dos pacientes, inclusive a financeira (também considerada uma preocupação adicional Outros fatores devem ser levados em consideração quando se comparam as modalidades de TCTH, tais como: comorbidades, tempo entre o diagnóstico e a realização do transplante, estágio da doença na indicação do transplante, condições clínicas no diagnóstico, entre outros. Um estudo de coorte que avaliou a carga de trabalho de enfermagem em transplante de célulastronco hematopoiéticas (13) demonstrou que para ambas as modalidades de TCTH, autólogo e alogênico, o grau de gravidade foi semelhante no período de condicionamento, dia da infusão e na "pega" medular, entretanto, os pacientes submetidos ao autólogo apresentaram maior gravidade no período de pancitopenia em relação aos submetidos ao alogênico. Outros estudos que avaliaram a QV sugerem que não há diferença significativa entre as modalidades de transplante realizadas (14)(15) .…”
Section: Discussionunclassified